Dangerous Giving in Nineteenth-Century American Literature - Urakova, Alexandra (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores the dark, unruly, and self-destructive side of gift-giving as represented in nineteenth-century literary works by American authors. It asserts the centrality and relevance of gift exchange for modern American literary and intellectual history and reveals the ambiguity of the gift in various social and cultural contexts, including those of race, sex, gender, religion, consumption, and literature. Focusing on authors as diverse as Emerson, Kirkland, Child, Sedgwick, Hawthorne, Poe, Douglass, Stowe, Holmes, Henry James, Twain, Howells, Wilkins Freeman, and O. Henry as well as lesser-known, obscure, and anonymous authors, Dangerous Giving explores ambivalent relations between dangerous gifts, modern ideology of disinterested giving, and sentimental tradition.
1 Introduction -- 2 Gifts, Language, Ideology, and the Sentimental -- 3 Sentimental "Potlatch" and the Making of the Nation -- 4 Un-Gendering the Gift Book -- 5 Racial Identity and the Perils of Giving -- 6 The Poison of the Gift, The Race of the Gift -- 7 Pure Tokens and Venomous Bodies -- 8 The Gift/Gifts of Death -- 9 "The Season of Gifts": Christmas and Melancholia -- 10 Conclusion.
Keywords: America-Literatures.; Literature, Modern-19th century; Anthropology and the arts; North American Literature; Nineteenth-Century Literature; Anthropology of the Arts